Criteria for Small and Medium Entrepreneurship and Characteristics of the Business Climate in the Service Sector - Akhmedova Aziza Tokhirovna (International Journal on Orange Technologies, 2022)
The article reveals the features of the development trends of small and medium-sized businesses in the framework of the financial activity of entrepreneurship, outlines the features of the revival taking place, in the context of the revival of the business climate, based on determining the strategy mechanism and the efficiency of use in the service sector.